Neuroprotective Effects of a Cholecystokinin Analogue in the 1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine Parkinson’s Disease Mouse Model - Zhang, Zijuan; Li, Hai; Su, Yunfang; Ma, Jinlian; Yuan, Ye; Yu, Ziyang; Shi, Ming; Shao, Simai; Zhang, Zhenqiang; Hölscher, Christian (Frontiers in Neuroscience, 2022)
Parkinson's disease (PD) is a chronic neurodegenerative disease. Type 2 diabetes mellitus (T2DM) has been identified as a risk factor for PD. Drugs originally developed for T2DM treatment such as liraglutide have shown neuroprotective effects in mouse models of PD. Cholecystokinin (CCK) is a peptide hormone with growth factor properties. Here, we demonstrate the neuroprotective effects of the (pGLu)-(Gln)-CCK8 analogue in an acute PD mouse model induced by 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). Administration of CCK analogue (50 nmol/kg ip.) for 7 days after MPTP treatment improved the locomotor and exploratory activity of mice, and improved bradykinesia and movement balance of mice. The CCK analogue administration also restored tyrosine hydroxylase (TH) positive dopaminergic neuron numbers and synapse numbers (synaptophysin levels) in the substantia nigra pars compacta (SNpc). The CCK analogue decreased glia activation and neuroinflammation in the SNpc, and regulated autophagy dysfunction induced by MPTP. CCK analogue protected against mitochondrial damage and ER stress, and also decreased the ratio of apoptosis signaling molecules Bax/Bcl-2. Importantly, the CCK analogue improved the decrease of p-CREBS133 growth factor signaling in the SNpc. Therefore, the CCK analogue promotes cell survival of dopaminergic neuron in the SNpc by activating the cAMP/PKA/CREB pathway that also inhibits apoptosis and regulates autophagy impairment. The present results indicate that CCK analogue shows a promising potential for the treatment of PD.